Transparansi Penyaluran Dana Program Keluarga Harapan (PKH) di Nagari Pakan Rabaa Utara - Tiara Angreini; Syamsir Syamsir (Al-DYAS, 2026)
Transparency in the distribution of social assistance funds is an important principle in realizing good governance, particularly in the Family Hope Program (PKH), which is intended for underprivileged communities. However, the implementation of transparency at the local level often has not run optimally. This study aimed to analyze the transparency of PKH fund distribution in Nagari Pakan Rabaa Utara, South Solok Regency. This study used a qualitative approach with a descriptive method. Data were obtained through in-depth interviews, observation, and documentation involving nagari officials, PKH facilitators, and beneficiary and non-beneficiary communities. The results showed that the transparency of PKH fund distribution in Nagari Pakan Rabaa Utara had not been implemented optimally. Information regarding beneficiary criteria, distribution mechanisms, and lists of beneficiaries had not been openly published and was not yet easily accessible to the community. This condition resulted in targeting inaccuracies, both in the form of inclusion errors and exclusion errors. The factors influencing the transparency of PKH fund distribution included weak availability and access to public information, limited use of information technology, and suboptimal mechanisms for community monitoring and complaints. Thus, strengthening the transparency of PKH fund distribution requires the commitment of officials, information disclosure, and active community involvement so that social assistance program governance becomes more accountable, well-targeted, and equitable.